Cord gamma glutamyl transpeptidase activity and neonatal jaundice. Issue 4 (April 1976) - Davidson, D C; McIntosh, W B; Ford, J A
Abstract : gamma Glutamyl transpeptidase (GGT) activity was measured in normal neonates and in maternal serum post partum. Levels were above the normal adult range (35I U/1) in all neonates and a significant correlation was bound between enzyme activity and bilirubin levels on day 7(P less than 0-005). The mean bilirubin level on days 4 and 7 was higher in babies with cord values less than 90 IU/1. In certain circumstances increased plasma GGT activity may serve as an index of enzyme induction. However, our results suggest that raised levels in the neonate may reflect hepatic microsomal damage with subsequent impairment of bilirubin conjugation. Further evaluative studies of cord GGT activity in neonates at risk, with a view to early prophylactic or therapeutic measures, are indicated.